Mechanics, Ionics, and Optics of Metal–Organic Framework and Coordination Polymer Glasses - Horike, Satoshi; Ma, Nattapol; Fan, Zeyu; Kosasang, Soracha; Smedskjaer, Morten M (Nano letters, 2021)
Melt and glassy states of coordination polymers (CPs)/metal–organic frameworks (MOFs) have gained attention as a new class of amorphous materials. Many bridging ligands such as azolate, nitrile, thiocyanide, thiolate, pyridine, sulfonate, and amide are available to construct crystals with melting temperatures in the range of 60–593 °C. Here, we discuss the mechanism of crystal melting, glass structures, and mechanical properties by considering both experimental and theoretical studies. High and exclusive H+ or Li+ conductivities in moldable CP glasses have been proven in the all-solid-state devices such as fuel cells or secondary batteries. Transparent glasses with wide composition and available dopants are also attractive for nonlinear optics, photoconductivity, emission, and light-harvesting. The ongoing challenge in the field is to develop the design principles of CP/MOF melts and glasses, corresponding functions of mass (ion, electron, photon, phonon, and so forth). transport and conversion, and the integration of devices with the use of their tunable mechanical properties.